Interdisciplinary Research Drivers and Serendipity Factor: An Applied Mechanics Perspective on Some Past Application Platforms (International Journal of Automation and Smart Technology, 2014)
In recent years, academia, research institutes, and industry have placed an increasing emphasis on interdisciplinary research, with a special focus on Applied Mechanics due to its influence on many emerging fields. Leaders in the Applied Mechanics field have emphasized the need to create an appropriate interdisciplinary organization, either through a matrix organization or with a formal organization. This paper reflects on the lessons learned from the inception, rise and evolution of the field of Theoretical & Applied Mechanics at various universities and institutes around the world. In this way, we can obtain a better understanding of the driving forces of one type of interdisciplinary research. Collaboration and competition between the various disciplinary research institutes and the more traditional engineering/applied sciences departments will be discussed. Based on a series of research and development experiences and using Nano-BioMEMS/NEMS, smart structure, and electret application platforms, we discuss the theoretical architectures and corresponding applications to further strengthen our claim that successful interdisciplinary applied science research requires the establishment of strong industries. We also account for an added serendipity factor, which suggests that a prepared, well-trained open mind, connected to other collaborative research efforts, has the ability to seize new opportunities for innovation as they arise. Examples from past research provide suggestions on how to further improve interdisciplinary research. Other factors including the influence of an interdisciplinary organizational structure, collaborative teamwork framework, and the influence of online interaction with an exchange of ideas are also discussed.